Predicting fluid responsiveness using change in pulse pressure variation and stroke volume variation after tidal volume challenge in postoperative patients receiving lung protective ventilation - Pimsai Kunakorn (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND. Background: Lung protective ventilation with low tidal volume (VT) is beneficial in patients with intermediate to high risk of post-operative pulmonary complications. However, during low VT ventilation, pulse pressure variation (PPV) and stroke volume variation (SVV) do not predict fluid responsiveness. Objective: To determine whether changes in PPV and SVV after transient increases in VT could predict fluid responsiveness. Materials and Methods: The authors recorded 20 measurements from 15 patients experiencing post-operative acute circulatory failure. The authors performed a VT challenge by transient increasing VT from 6 to 8 mL/kg (VT6-8), 8 to 10 mL/kg (VT8-10), and 6 to 10 mL/kg (VT6-10) of patients' predicted body weight. The change in PPV (ΔPPV) at VT6-8 (ΔPPV6-8), VT8-10 (ΔPPV8-10), VT6-10 (ΔPPV6-10), and the change in SVV (ΔSVV) at VT6-8 (ΔSVV6-8), VT8-10 (ΔSVV8-10), and VT6-10 (ΔSVV6-10) were recorded. Patients were classified as fluid responders if there was an increase in stroke volume of more than 10% after a fluid bolus. Results: Following the VT challenge, ΔPPV and ΔSVV failed to predict fluid responsiveness, with areas under the receiver operating characteristic curves (with 95% confidence intervals) of 0.49 (0.23 to 0.74), 0.54 (0.29 to 0.79), 0.52 (0.28 to 0.77) for ΔPPV6-8, ΔPPV8-10, and ΔPPV6-10, and 0.55 (0.30 to 0.80), 0.55 (0.31 to 0.80), and 0.59 (0.34 to 0.84) for ΔSVV6-8, ΔSVV8-10, and ΔSVV6-10, respectively. Conclusion: Changes in PPV and SVV after the VT challenge did not predict fluid responsiveness in post-operative patients with low VT ventilation.